2012
DOI: 10.1007/s12070-012-0555-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thyroidectomy in Advanced Laryngeal and Pharyngolaryngeal Carcinoma

Abstract: Total thyroidectomy or hemithyroidectomy together with a total laryngectomy (TL) or pharyngo laryngectomy (TPL) for (pharyngo) laryngeal cancer often renders the patient hypothyroid and commits them to life-long thyroid hormone replacement. To determine the incidence of thyroid gland invasion (TG) in patients undergoing TL or TPL with total thyroidectomy (TThy) or lobectomy (HThy) for advanced laryngeal or hypo pharyngeal cancer and to assess predicative factors. Retrospective analysis of 35 patients from 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Thyroid gland invasion is part of the extension of anterior extralaryngeal cancer . As reported by Chen et al, the most common route of extralaryngeal spread of glottic SCC is through the cricothyroid membrane .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thyroid gland invasion is part of the extension of anterior extralaryngeal cancer . As reported by Chen et al, the most common route of extralaryngeal spread of glottic SCC is through the cricothyroid membrane .…”
Section: Discussionmentioning
confidence: 95%
“…Thyroid gland invasion is part of the extension of anterior extralaryngeal cancer. 1,2,[9][10][11][12][13][14] As reported by Chen et al, the most common route of extralaryngeal spread of glottic SCC is through the cricothyroid membrane. 15 CT scan sensitivity is low for thyroid cartilage or cricothyroid membrane invasion, which were associated with TGI in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Ipsilateral hemithyroidectomy in advanced hypopharyngeal and laryngeal cancer is supported by literature demonstrating superior oncological control. 12 , 17 Basheeth et al 6 also demonstrated a significant relationship between tumor stage (pT4) and hypocalcaemia ( P = 0.05), but not with extent of thyroidectomy or pharyngectomy, while others have suggested pharyngectomy as a risk. 5 Comparatively, rates in the total and partial pharyngectomy subgroups reveal a higher permanent and transient hypocalcaemia rate for those undergoing total pharyngectomy.…”
Section: Discussionmentioning
confidence: 97%
“…The thyroid gland is located in the lymphatic drainage pathway of the larynx which adds to the risk of lymphatic invasion of the gland by malignant laryngeal tumors. For these reasons, it has been routinely practiced performing HT or TT together with TL for the management of LC [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Primary and salvage total laryngectomy (TL) are commonly performed for the management of laryngeal carcinoma (LC) [1]. The management of a clinically negative thyroid gland during TL remains to be an issue of controversy [2,3]. Most surgeons prefer to perform hemithyroidectomy (HT) on the ipsilateral side of the tumor.…”
Section: Introductionmentioning
confidence: 99%